2001
DOI: 10.1111/j.1365-2656.2001.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Population density of migratory and resident brown trout (Salmo trutta) in relation to altitude: evidence for a migration cost

Abstract: 1.For anadromous salmonids, the positive relations found in previous studies between adult size/age and stream characteristics suggest that the migration cost increases with stream length, water discharge and the altitude of the spawning site. In this study we hypothesized that the altitude of the spawning site is positively related to the migration effort. 2. Life-history theory predicts (i) that the equlibrium egg density, which is a fitness measure, thereby will decline more rapidly with altitude in migrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 39 publications
4
68
0
Order By: Relevance
“…By contrast, the fitness of resident individuals is expected to be unrelated to distance from the sea, because they remain their entire life in their natal stream. Bohlin et al [32] showed that the fitness of resident brown trout, Salmo trutta, did not change with altitude, whereas the fitness of anadromous brown trout tended to decline with altitude, an indicator of migration cost in that study. Therefore, the threshold size at maturity in male salmonid parr is expected to decrease with distance from the sea, an indicator of migration cost, to promote residency.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the fitness of resident individuals is expected to be unrelated to distance from the sea, because they remain their entire life in their natal stream. Bohlin et al [32] showed that the fitness of resident brown trout, Salmo trutta, did not change with altitude, whereas the fitness of anadromous brown trout tended to decline with altitude, an indicator of migration cost in that study. Therefore, the threshold size at maturity in male salmonid parr is expected to decrease with distance from the sea, an indicator of migration cost, to promote residency.…”
Section: Discussionmentioning
confidence: 99%
“…Age-0 fish at lowerelevation sites within our study streams emerged 9-15 d earlier than those at upper-elevation sites within the same streams (K.E.M., unpublished data). Third, the spawning areas used by larger, migratory adults within individual streams may be lower than the areas used by smaller, resident adults (Averett and MacPhee 1971;Bohlin et al 2001). Because larger females tend to have larger eggs, they are also likely to produce larger offspring (Einum and Fleming 1999).…”
Section: Causes Of Variationmentioning
confidence: 99%
“…More importantly, it may promote diversification of life history strategies within and among populations (Jonsson et al 1988;Conover and Schultz 1995;Bohlin et al 2001) and contribute to population stability and long-term survival in temporally variable environments (den Boer 1968; Chandler and Bjornn 1988;Good et al 2001;Kendall and Fox 2002).…”
Section: Implications For Conservation Managementmentioning
confidence: 99%
“…However, mid-summer densities in the downstream reach were relatively low (0. (Kelly & Dick 2005), and 1.18 fish m~2 in a Swedish stream (Bohlin et al 2001). Space limitation is thought to occur at much higher densities (Grant & Kramer 1990).…”
Section: Discussionmentioning
confidence: 98%